2007
DOI: 10.5194/aab-50-374-2007
|View full text |Cite
|
Sign up to set email alerts
|

Hair whorls of Holstein Friesian heifers and affects on growth and behaviour

Abstract: Abstract. The aim of this study was to investigate whether the growth, number of crossed squares in the open-field test and time of traversing the maze in the maze are affected by the height position of they facial whorl in heifers which were kept in experimental conditions. Fifty-eight Holstein heifers were used. The hair whorl position was determined as hair whorl high, middle and low. Heifers with a high whorl had significantly higher body weight at days 360 (P<0.05) and 540 (P<0.01) and average daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Research findings from the last sixteen years (Grandin, et al, 1995;Randle, 1998;Lanier, et al, 2001;Broucek, et al 2007) suggested that facial hair whorl position and shape in bulls may be related to their behaviour, in particular their temperament. This is attributed to the fact that during embryonic development, skin, its products and the nervous system arise from the same germ layer, or ectoderm (Fletcher and Weber, 2010).…”
Section: Adamczyk Et Al: Effect Of Behaviour Of Holstein-friesian Anmentioning
confidence: 99%
“…Research findings from the last sixteen years (Grandin, et al, 1995;Randle, 1998;Lanier, et al, 2001;Broucek, et al 2007) suggested that facial hair whorl position and shape in bulls may be related to their behaviour, in particular their temperament. This is attributed to the fact that during embryonic development, skin, its products and the nervous system arise from the same germ layer, or ectoderm (Fletcher and Weber, 2010).…”
Section: Adamczyk Et Al: Effect Of Behaviour Of Holstein-friesian Anmentioning
confidence: 99%
“…A number of authors have suggested that the environment and farm management could influence the behaviour of animals in a variety of ways, including their responses to potentially stressful situations [20,3,21,10].…”
Section: Introductionmentioning
confidence: 99%
“…Only about 10% of calves, particularly from small herds, are fed native milk until weaning (Krohn et al, 1999). Apart from immediate welfare problems, the early separation of dam and calf has negative implications for the health of cow, calf diseases, high susceptibility to stress, and instability of the former social behaviour (Brouček et al, 2008).…”
mentioning
confidence: 99%